Foreign Banks in Poor Countries : Theory and Evidence - Detragiache, Enrica; Gupta, Poonam; Tressel, Thierry (Washington, D.C. : International Monetary Fund, 2006)
We study how foreign bank penetration affects financial sector development in poor countries. A theoretical model shows that when foreign banks are better at monitoring highend customers than domestic banks, their entry benefits those customers but may hurt other customers and worsen welfare. The model also predicts that credit to the private sector should be lower in countries with more foreign bank penetration. In the empirical section, we show that, in poor countries, a stronger foreign bank presence is robustly associated with less credit to the private sector both in cross-sectional and panel tests. In addition, in countries with more foreign bank penetration, credit growth is slower and there is less access to credit. We find no adverse effects of foreign bank presence in more advanced countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet